Impact of Chronic Obstructive Pulmonary Disease on Postoperative Complications Following Simultaneous Bilateral Total Knee Arthroplasty - Gu, Alex; Wu, Shitong; Mancino, Fabio; Liu, Jiabin; Ast, Michael P.; Abdel, Matthew P.; Sculco, Peter K. (The Journal of Knee Surgery, 2019)
For patients who qualify, simultaneous bilateral total knee arthroplasty (TKA) is a viable option for the treatment of bilateral symptoms. However, the incidence of chronic obstructive pulmonary disease (COPD) has been steadily rising over the past few decades and may impact those who qualify as candidates for bilateral TKA. As such, the aim of this study was to determine the impact of COPD on postoperative outcomes in patients who receive simultaneous bilateral TKA. A retrospective cohort study was conducted utilizing data provided through the American College of Surgeons National Surgical Quality Improvement Program. All patients who had undergone simultaneous bilateral TKA between 2007 and 2016 were identified and further stratified into groups based upon the COPD status. Incidence of adverse events after TKA in the acute postoperative period was evaluated with univariate and multivariate analyses. COPD was found to be an independent risk factor for the development of major (odds ratio [OR]: 2.5; p = 0.015), renal (OR: 5.1; p = 0.02), and thromboembolic complications (OR: 2.5; p = 0.027). In addition, patients with COPD were at increased risk for having an extended hospital length of stay (LOS; p < 0.001) and development of urinary tract infections (p < 0.001). Patients with COPD are at higher risk for development of overall major complications, as well as renal and thromboembolic complications after simultaneous bilateral TKA. Interestingly, patients were not at increased risk for the development of pulmonary or wound complications. When considering a staged versus simultaneous bilateral TKA, surgeons should be aware of the impact COPD status has on the postoperative complication rate.
Keywords: simultaneous bilateral total knee arthroplasty; chronic obstructive pulmonary disease; postoperative complications; length of stay; urinary tract infection